2011
DOI: 10.1258/msl.2010.010072
|View full text |Cite
|
Sign up to set email alerts
|

The responses of professional groups to the use of Section 136 of the Mental Health Act (1983, as amended by the 2007 Act) in Gloucestershire

Abstract: There is a gap in the expectations of the different agencies involved in the S136 process, which have the potential to be divisive if interagency pathways and agreements are not in place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This was in line with the findings of other studies of the experience of detention in which people have described feeling as though they were being punished and criminalised. 10,1719 The use of custody as a place of safety was cut drastically in Sussex between 2015 and the enactment of the PCA in December 2017. Ten people were detained to custody in the month prior to the amendments coming in to effect, and it has not been used at all since December 2017.…”
Section: Resultsmentioning
confidence: 99%
“…This was in line with the findings of other studies of the experience of detention in which people have described feeling as though they were being punished and criminalised. 10,1719 The use of custody as a place of safety was cut drastically in Sussex between 2015 and the enactment of the PCA in December 2017. Ten people were detained to custody in the month prior to the amendments coming in to effect, and it has not been used at all since December 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Local and national stakeholders, both professionals and people with lived experience engaged in the above study, confirmed that repeated detention was a significant issue that was felt to deserve further investigation. National data on repeated detention is not available as there is no requirement to measure or report on recurrence and very little research has examined this aspect of S136, despite many studies having indicated incidence of fewer people detained than the number of detentions examined [14,15,16,17]. However, two small studies have specifically focussed on the subject, both concluding that there was a strong correlation between those detained recurrently and the diagnoses of personality disorder, in the latter case, specifically emotionally unstable personality disorder [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The collusion between the parties can have implications for the waiting time for detainees in need of immediate care and support. These findings were similarly noted in Burgess et al 5 and Riley et al 6 and is at odds with key recommendations from the Royal College of Psychiatrists’ section 136 national guidance. According to these guidelines: 136 suites should agree to accept an individual before the emergency services begin their journey and have the necessary staff on hand to receive individuals without delay or recourse to emergency professionals.…”
Section: Discussionmentioning
confidence: 53%
“…There was a general consensus regarding the improvement of training to enable emergency workers to feel more confident in recognising how mental health problems can present, dealing with crises and engaging with individuals affected. 6,14,19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation